AKUNTANSI SUMBERDAYA MANUSIA: ANTARA HIDUP DAN MATI - -, Rispantyo - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2009)
Abstract The practice accounting expands along with blooming economics. One of the existences of growth of practice accounting is human resource accounting. There are some logical reason able to be used as basis for apply the human resource accounting. The reason for example, that to form the resource human having membership coasted money big, individual value in organization, or as walking of era of information technology in this time, human resource become the its top attention. On the applying, human resource accounting experience of the resistance. The resistance especially it him because do not of is existence of agreement in measurement assess the human resource, what later will be mentioned in balance. Till now, this human resource accounting not yet been applied, so that its status we can say " between this and deadâ€. The writing life try to give the brain-storming for the can "to living of" human resource accounting, what is expected can improve the quality of financial statement in the case of economic decision making. Besides, do not theory development ought to "dead", but continued useful till and can answer the new question of arising out. Keywords: human resource accounting, financial statement